Computer forensies : jumpstart - Solomon, Michael [ (Michael G.)] , 1963- (Wiley Publishing, 2011)
A guide to computer forensics provides information on such topics as conducting a forensics investigation, finding hidden data, capturing images, collecting and preserving computer evidence, and using computer forensic tools.